Marketing Strategy To Improve The Competitiveness Of A Chocolate Drink Business In Surabaya - Safa’at Safa’at; Nuzulul Fatimah; Leonard Adrie Manafe (LPPPIPublishing, 2023)
This study aims to find out how the marketing strategy is using SWOT Analysis in Chocolate Beverage Product Businesses to increase Competitiveness. This study uses a descriptive qualitative approach and SWOT analysis to take advantage of opportunities, maximize strengths, reduce weaknesses, and avoid threats. The results of this SWOT analysis indicate that the chocolate beverage business is implementing a Strength Opportunity (SO) strategy, this is a strategy for chocolate beverage businesses to take advantage of strengths and opportunities to run their business. Therefore, chocolate beverage business to meet the tastes and needs of the community, it is necessary to maintain and improve chocolate beverage products that have a variety and distinctive tastes. To attract more loyal customers, there is creativity in using technology to market products online, to expand the product marketing network for the chocolate drink business.